Kemitraan Pemerintah Swasta dalam Penerapan Peraturan Daerah Kota Pekanbaru Nomor 08 Tahun 2014 tentang Sampah - Ben Hansel Notatema Zebua; Adlin Adlin; Fadhilatun Nissa (Mahesa Research Center, 2023)
This article discusses the concept of collaborative governance in the implementation of Pekanbaru City Regional Regulation Number 08 of 2014 concerning Waste. The waste problem in Pekanbaru City is a public problem faced by local governments, especially Pekanbaru City. The research method used is literature study by reading and exploring various documentation that discusses the main issues and concepts in this study. The results of the study show that the Public Private Partnership (PPP) pattern is a form of collaborative governance in waste management through the implementation of Pekanbaru City Regional Regulation Number 08 of 2014 concerning Waste. In the provision of public services through the PPP pattern, there are four aspects to consider in the provision of public services, namely (a) the potential aspect of the implementation of the PPP, (b) the aspect of the potential obstacles to the PPP scheme, (c) the aspect of analyzing the benefits and costs of the PPP pattern, and the aspect of the private sector's interest in the provision public service.